ELECTRICAL CURRENT LIMITING TOOL USING ARDUINO MICROCONTROLLER - Meiman Belala Zendrato; Siti Anisah; Adi Sastra P. Tarigan (INFOKUM, 2022)
THe electric current limiter serves to limit the use of electricity in each room so that it does not affect electricity usage activities that occur outside the room. Restrictions can be done using an Arduino microcontroller by utilizing the ACS712 sensor in reading the use of current passing through the cable. This prototype is made with the ability to withstand a 200-watt electrical load so that in the event of excessive use, the Arduino will signal to the relay to take the action of disconnecting the electric current. The relay will disconnect the electric current within a few seconds to give the user the opportunity to reduce the load used through the cable. The relay will then turn on again and Arduino will check the electric current again and if there is no decrease in the use of electric current, then Arduino will again give a breaker signal to the relay.